Iatrogenic immunodeficiency-associated lymphoproliferative disorders in transplant and nontransplant settings - Matthew G.S. Kubica; Nikhil A Sangle (Wolters Kluwer Medknow Publications, 2016)
Iatrogenic immunodeficiency-associated lymphoproliferative disorders comprise a group of lymphoid neoplasms that are associated with an immunosuppressed state, either in the posttransplant period, or during the treatment of various autoimmune and rheumatologic disorders by immunomodulatory medications. Their morphologies vary widely but are generally classified according to the lymphomas that they most closely resemble. This group is strongly associated with infections by the Epstein-Barr virus as a result of impaired immune function in the immunosuppressed state. Although further classification may become necessary in the coming years, they are distinguished from lymphomas in immunocompetent hosts because reduction or cessation of immunosuppressive or immunomodulatory therapy can result in complete clinical remission.